2011
DOI: 10.1016/j.bbamcr.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear import by karyopherin-βs: Recognition and inhibition

Abstract: Proteins in the Karyopherinβ family mediate the majority of macromolecular transport between the nucleus and the cytoplasm. Eleven of the 19 known human Karyopherinβs and 10 of the 14 S. cerevisiae Karyopherinβs mediate nuclear import through recognition of nuclear localization signals or NLSs in their cargos. This receptor-mediated process is essential to cellular viability as proteins are translated in the cytoplasm but many have functional roles in the nucleus. Many known Karyopherinβ-cargo interactions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
386
2
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(410 citation statements)
references
References 213 publications
(218 reference statements)
5
386
2
10
Order By: Relevance
“…However, several technical obstacles have rendered the systematic mapping of cargo–NTR relationships challenging: (i) The transient nature of cargo–NTR interactions makes them largely inaccessible to biochemical identification by NTR‐centric affinity purification; (ii) each NTR does recognize a multitude of cargos and their cargo spectrum might overlap; and (iii) cargo abundances (copy numbers per cell) span several orders of magnitude in situ . The vast majority of previous studies therefore were designed in a cargo‐centric manner and have reported transport pathways for individual cargos (for review, see, e.g., Chook & Süel, 2011; Kimura & Imamoto, 2014; Twyffels et al , 2014). Although powerful for studying the contribution of the nuclear transport system to individual cellular mechanisms, these approaches are not suitable to comprehensively chart its cargo spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…However, several technical obstacles have rendered the systematic mapping of cargo–NTR relationships challenging: (i) The transient nature of cargo–NTR interactions makes them largely inaccessible to biochemical identification by NTR‐centric affinity purification; (ii) each NTR does recognize a multitude of cargos and their cargo spectrum might overlap; and (iii) cargo abundances (copy numbers per cell) span several orders of magnitude in situ . The vast majority of previous studies therefore were designed in a cargo‐centric manner and have reported transport pathways for individual cargos (for review, see, e.g., Chook & Süel, 2011; Kimura & Imamoto, 2014; Twyffels et al , 2014). Although powerful for studying the contribution of the nuclear transport system to individual cellular mechanisms, these approaches are not suitable to comprehensively chart its cargo spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Most nucleocytoplasmic transport of proteins in the cell is carried out by the Karyopherin-β (Kapβ) family of nuclear transport proteins, which recognize nuclear-localization signals (NLS) and nuclear-export signals (NES) on other proteins to carry out such transport [37][38][39]. Pedraza et al (1997) showed that not only is 21.5-kDa MBP located in the nucleus of OLGs, it is actively transported there, in an energy-as well as temperature-dependent process [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…The first classical NLS is composed of 1 or 2 stretches of positively-charged amino acids, often lysine-rich [39,42]. Another type is the bipartite NLS, which consists of two basic residues, a spacer consisting of 10 residues, and another basic region consisting of at least three basic residues out of five [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further biological analysis clarified that cytoplasmic receptors (importin families [48,49] or others [50]) recognized the NLS or the 3-demensional structure of the protein, and then form a complex that can pass through the nuclear pore complex (NPC) [51]. One of the typical NLS is derived from the SV40 T-antigen (NLS SV40 ): PKKKRKV [52].…”
Section: Control Of the Intracellular Trafficking For Pdna Deliverymentioning
confidence: 99%